0n Fuzzy Soft (α,β)-class(Q)operator - Hanan Khalid (Wasit Journal of Computer and Mathematics Science)
this paper present a new type of operator , referred to as the fuzzy soft class (Q) operator , which operator on a complex Hilbert space . we examin several advantageous properties that are exclusive this operator class.